2018
DOI: 10.1371/journal.pone.0207928
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with time to first healthcare visit, diagnosis and treatment, and their impact on survival among breast cancer patients in Mali

Abstract: ObjectiveTo analyse patient and healthcare system related factors influencing the time to first healthcare visit, diagnosis and treatment of breast cancer patients in sub-Saharan Africa and the impact on survival in order to advise on early detection strategies.MethodsA prospective hospital cohort study was conducted at the only pathology department in Mali, at the University Hospital in Bamako. All the female patients with a breast cancer diagnosis between January and April 2016 were interviewed with a struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
64
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 34 publications
8
64
4
2
Order By: Relevance
“…Similarly, compared with studies in sub-Saharan African countries, the median patient interval in our study (30 days) was considerably shorter than those reported from Rwanda (150 days)24 and Mali (144 days),34 but comparable with that reported from South Africa (23 days) 35. As expected, compared with findings from countries outside of sub-Saharan Africa, however, our finding of median patient interval is generally longer 36 37…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similarly, compared with studies in sub-Saharan African countries, the median patient interval in our study (30 days) was considerably shorter than those reported from Rwanda (150 days)24 and Mali (144 days),34 but comparable with that reported from South Africa (23 days) 35. As expected, compared with findings from countries outside of sub-Saharan Africa, however, our finding of median patient interval is generally longer 36 37…”
Section: Discussionsupporting
confidence: 80%
“…Our finding of median diagnostic interval (69 days) was lower than that reported in Rwanda (150 days)24 but longer than those reported in Mali (27 days)34 and South Africa (28 days) 35. Sixty-nine percent of the patients in our study waited for >30 days, and 18% for over a year to receive diagnostic confirmation following first medical consultation for their disease.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Despite the fact that we included patients from the three largest hospitals in Mozambique, detailed follow-up data were only available for patients treated at the MCH. Yet, this single-centre subcohort is similar to other African series in terms of young age at diagnosis, 40 high prevalence of HIV infection, 15 long delays between symptoms and diagnosis 41 and a large proportion of stage III/IV. 3 The limited staging options available (chest X-ray and abdominal ultrasound) may have led to an underestimation of the real incidence of stage IV disease, which may partly explain the low survival of our patients.…”
Section: Discussionsupporting
confidence: 59%
“…33 Elsewhere in Africa, and notably, in West Africa, the appraisal of the role of the healers in cancer care is far less favorable and it is often considered that they contribute to the late diagnosis and care process implementation or to the absconsion of patients. [34][35][36][37] Recent medical literature from Africa drew the attention of the medical community on this problem and it is possible that Africa will enter soon in a period of medical history already observed in Europe where modern medical power installation conducted to the elimination of "illegal" healers. 38 Given the importance of liver diseases in SSA (often >10% of the general population is concerned in most countries), the common practice of tradi- tional healers is, of course, often dedicated to patients affected with chronic hepatitis ie at risk to develop terminal complications such as liver cirrhosis or PLC.…”
mentioning
confidence: 99%